Cr(III) and Cr (VI) REMOVAL FROM WASTE WATER BY AMBERLITE IRN150 - Bounab, N. A; Boukhalfa, C (university of el oued/جامعة الوادي, 2021)
The aim of this work is the use of Amberlite IRN 150 resin in the removal of Cr (III) and Cr (VI) from tanning and chrom e plating waste water s respectively Removal experiments were carried out in ba tch Kenitics and equilibrium studies were undertaken using various models The obtained results show that the increase in pH implies an increase of Cr (III) removal in tanning water and a decrease of Cr (VI) removal in chrome plating water. In the two cases , t he exchange kinetics is well described by the second order model . The removal of the two ions by IRN150 is not limited by intraparticular diffusion. The Freundlich isotherm is more suitable for describing Cr(III) removal in tanning water . H owever, in ch rom e plating water , Cr (VI) removal is better described by the Langmuir isotherm.
ARTICLE
Keywords: Keywords: Cr(III) Cr(VI) Amberlite IRN150 ; Tanning Chrome plating Water treatement